Dampak Konsumsi Kopi terhadap Respons Cold Pressor Test pada Mahasiswa Kedokteran Universitas Tarumanagara: Studi Komparatif - Nikita Tan; Susy Olivia Lontoh (Pusat riset dan Inovasi Nasional, 2024)
Caffeine contained in coffee has a stimulating effect on the sympathetic nervous system, which can influence blood pressure. The Cold Pressor Test (CPT) is a method used to measure blood pressure response to cold-induced stress. This study aimed to compare the mean blood pressure between coffee-drinking and non-coffee-drinking medical students after undergoing the CPT. This research employed a quantitative experimental design with a cross-sectional approach, involving 89 students from the Faculty of Medicine at Universitas Tarumanagara. Subjects were divided into two groups: coffee drinkers and non-coffee drinkers. Blood pressure measurements were taken before and after the CPT intervention. The results showed that both systolic and diastolic blood pressure increased significantly in both groups after CPT. However, the increase in mean blood pressure, particularly diastolic pressure, was significantly higher in the coffee-drinking group compared to the non-coffee-drinking group (p < 0.05). These findings indicate that coffee consumption prior to CPT contributes to a greater blood pressure response. Therefore, it can be concluded that there is a significant difference in mean blood pressure between coffee drinkers and non-coffee drinkers following the Cold Pressor Test.